An Analysis of Expressive Speech Acts Used in Ellen Show " Interview with Billie Eilish" - Ngasini, Ngasini; Senowarsito, Senowarsito; Nugrahani, Dyah (Allure Journal, 2021)
This research aims to identify types of expressive speech acts, to describe the realization and the actual condition used in Billie Eilish interview's in Ellen show. The researcher used descriptive qualitative. The data of this study collected from the interview script. In this research, the data are taken from the dialogue among the Interviewer and Interviewee; this research used document analysis for analyzing the data. The finding showed there were 16 utterances of expressive speech acts, which consisted of 1 expression of apologizing (6,2 %), 1 expression of thanking (6,2 %), 6 expression of congratulating (37,5),1 expression of greeting (6,2%), 1 expression of wishing (6,2%), 5 expression of attitudes (31,2%). The result showed the expressive of congratulating are the most dominant expressive speech act he expressive of congratulating are the most dominant expressive speech act.